The Effect of Using QRIS in the Collection of Zakat, Infaq, and Alms on Economic Growth in Indonesia: An Econometric Analysis - M. Yusril Kholik (Jurnal Magister Ekonomi Syariah, 2025)
This study analyzes the dynamic relationship between the use of QRIS, the collection of zakat, infaq, and alms (ZIS), and economic growth in Indonesia. It contributes to the empirical understanding of ZIS as a key transmission channel linking digital payment innovation to macroeconomic growth. A quantitative approach was employed using the Vector Autoregression (VAR) model, which utilized quarterly data from 2019 to 2024. The procedures included stationarity tests, optimal lag selection, Granger causality tests, Variance Decomposition (VDC), and Impulse Response Function (IRF) analyses to examine causal links, variable contributions, and short- and long-term dynamics. The results indicate that QRIS has a significant effect on ZIS (coefficient 0.004; t-statistic 2.140; p-value 0.036), and ZIS has a significant influence on economic growth (coefficient 0.012; t-statistic 2.025; p-value 0.044). However, the direct impact of QRIS on GDP is insignificant, suggesting that QRIS drives economic growth indirectly through the intermediation of ZIS. Granger causality tests confirm one-way causality from QRIS to ZIS and from ZIS to GDP. VDC analysis shows that ZIS’s contribution to GDP variation rises from 12.48% in the initial period to 31.29% in the long term, while QRIS’s direct contribution remains limited. The IRF results further reveal a positive and sustained ZIS response to QRIS shocks, as well as a robust GDP response to ZIS shocks. Overall, the effectiveness of QRIS in promoting growth depends on strengthening ZIS collection and productive distribution. Integrating Islamic financial digitalization with ZIS intermediation accelerate inclusive and sustainable economic development.